2017
DOI: 10.2196/games.6894
|View full text |Cite
|
Sign up to set email alerts
|

Development, Usability, and Efficacy of a Serious Game to Help Patients Learn About Pain Management After Surgery: An Evaluation Study

Abstract: BackgroundPostoperative pain is a persistent problem after surgery and can delay recovery and develop into chronic pain. Better patient education has been proposed to improve pain management of patients. Serious games have not been previously developed to help patients to learn how to manage their postoperative pain.ObjectiveThe aim of this study was to describe the development of a computer-based game for surgical patients to learn about postoperative pain management and to evaluate the usability, user experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 45 publications
1
36
0
3
Order By: Relevance
“…For clarity of discussion, we first divide pain types into two categories, i.e., acute and chronic pain. It was found that 25 publications presented apps for pain management that were relevant to chronic pain, and two research papers proposed solutions for acute pain management [22,23]. Under the chronic pain condition, three apps were for general chronic pain type [16,24,25], and 22 apps were for disease/regional-specific pain type.…”
Section: Pain Typementioning
confidence: 99%
See 2 more Smart Citations
“…For clarity of discussion, we first divide pain types into two categories, i.e., acute and chronic pain. It was found that 25 publications presented apps for pain management that were relevant to chronic pain, and two research papers proposed solutions for acute pain management [22,23]. Under the chronic pain condition, three apps were for general chronic pain type [16,24,25], and 22 apps were for disease/regional-specific pain type.…”
Section: Pain Typementioning
confidence: 99%
“…Nine publications (33% of the studies) [16,22,23,28,30,37,40,41,45] mentioned that the potential users had an average to high technology literacy level for mobile devices, while three publications (11% of studies) [27,31,44] showed that the proposed app was designed for patients with low or no technology literacy. One app was designed for patients that can have any technology literacy level [46].…”
Section: Targeted Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…If that is the case, as between both measures the only intervention is the game, it can be concluded that the increase in that characteristic is due to the game effect, and therefore the game is formally validated. There are plenty of examples in literature that use this approach to validate serious games including, for instance: a game for children with autism to learn emotions [10], a game for patients to manage pain after surgery [11] or a game to raise awareness about bullying and cyberbullying [12].…”
Section: Serious Games Formal Validationmentioning
confidence: 99%
“…Dans le domaine de l'enseignement, les jeux sérieux apparaissent comme des outils pédagogiques innovants pour acquérir des compétences, notamment dans le domaine de la santé. Il s'agit d'applications logicielles utilisant les principes et la mécanique du ludique pour atteindre des objectifs sérieux tels que la formation ou la motivation à suivre un traitement médical par exemple [8], y compris pour la douleur [9].…”
unclassified